Recent Publications (Quarterly Journal of Economics, 1937)
Recent Publications Get access The Quarterly Journal of Economics, Volume 51, Issue 4, August 1937, Pages 720–724, https://doi.org/10.1093/qje/51.4.720 Published: 01 August 1937